O ALUNO COMO SUJEITO CENTRAL NO ENSINO: ELABORAÇÃO DE UM GUIA DIDÁTICO PARA O ENSINO CONTEXTUALIZADO DE BIOTECNOLOGIA NA REGIÃO CENTRO-SUL DO PARANÁ - Wiggers, Cleuni Fretta (2016)
The objective of this study was to provide a teaching guide containing examples of the region for the teaching of biotechnology in the Center-South of Paraná. For this work we attempted to reference the scientific knowledge, biology education, the teaching of biotechnology and the significant critical learning. The methodological approach of this study was quantitative and qualitative interpretative nature with participant observation. In an attempt to meet the goals the study steps are as follows: analysis of biology textbooks recommended by PNLEM / 2015; survey of biotechnological research in universities in the center-south region of the Paraná; preparation of supplementary brochure to textbook and implementation of this brochure. The data collection techniques were observation to note in observation forms, questionnaires and activities of the brochure. The research sample consisted of 101 students from three public school of the city of Laranjeiras do Sul. The results showed that it was possible to promote to high school students through the use of the brochure used to complement the textbook a significant learning of Biotechnology content, thereby providing the formation of a critical and active student, capable of positioning in face the discussions of the relevant topics the theme of Biotechnology.